Pelabelan Total Sisi Ajaib Pada Graf Anti-Fuzzy Bipolar 〖mC〗_n - Ilman Firmansa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This article discusses the edge magic total labeling of bipolar anti-fuzzy graphs. Bipolar anti-fuzzy graphs are seen as a new concept, therefore we adapt from previous research on the properties of magic labeling of bipolar anti-fuzzy graphs. The results show that, for every natural number, there exists a bipolar anti-fuzzy magic edge total labeling for mCn graphs.